2022
DOI: 10.1113/jp283469
|View full text |Cite
|
Sign up to set email alerts
|

Ketogenic diet‐induced weight loss occurs independent of housing temperature and is followed by hyperphagia and weight regain after cessation in mice

Abstract: support-information-section).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Notably, numerous long-term studies on low-carbohydrate, high-fat diets (LCHFD) have demonstrated weight loss despite the high caloric consumption [ 27 , 28 ]. However, our study reveals that transitioning from an LCHFD to a Western diet (WD) under isocaloric conditions also results in considerable weight regain, suggesting that the trigger for weight cycling lies in the return to a WD [ 29 ]. The impact of carbohydrates on weight gain has previously been suggested to be a central element in the development of obesity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Notably, numerous long-term studies on low-carbohydrate, high-fat diets (LCHFD) have demonstrated weight loss despite the high caloric consumption [ 27 , 28 ]. However, our study reveals that transitioning from an LCHFD to a Western diet (WD) under isocaloric conditions also results in considerable weight regain, suggesting that the trigger for weight cycling lies in the return to a WD [ 29 ]. The impact of carbohydrates on weight gain has previously been suggested to be a central element in the development of obesity.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that fluctuations in insulin levels in response to shifts in macronutrient intake may contribute to the development of weight cycling, thus explaining the weight regain phenomenon. Several studies have shown that LCHFD consumption significantly decreases insulin levels while WD consumption is associated with obesity development and high insulin levels [ 27 , 29 , 40 ]. Therefore, the return of a high-fat, high-sugar WD after LCHFD-induced weight loss could lead to hyperinsulinemia and promote weight regain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ketogenic diet consumption leads to weight loss in overweight and obese humans [ 37 ] and reduced weight gain in normal weight rodents [ 38 , 39 ], largely due to decreased food intake [ 40 ]. Consistent with the literature, our study found that both non-diabetic and STZ-diabetic keto-fed rats had lower bodyweights than the respective chow control animals.…”
Section: Discussionmentioning
confidence: 99%